THE POTENCY OF CARBON STROGE IN SEAGRASS Thalassia hemprichii IN NIRWANA BEACH PADANG CITY WEST SUMATERA PROVINCE - Shinta Maharani; Zulkifli Zulkifli; Bintal Amin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract Increased CO2 content causes an increase in greenhouse gas emissions in the atmosphere that cause global warming which then trigger climate change. One of the marine resources that acts as an absorber of CO2 in mitigating global warming is the seagrass ecosystem. In the waters of Nirwana Beach of West Sumatra, seagrass (Thalassia hemprichii) is one and only important types of seagrass. This study was conducted in December 2017-February 2018 in Nirwana Beach of Padang City West Sumatra, which aims to estimate the biomass, the average C-organic content and to identify the seagrass body part as the largest carbontrap as well as to estimate the relationship between the carbon storage and density of seagrass T. hemprichii. Sampling andmeasurement of water quality was done byusing quadratic transect at 3 stations. The results of the study showed that the largest biomass and largest carbon storge from all study sites were at the Bottom of Substrate (roots and rhizomes) with 315.46 gdw/m2 and 81.95 gC/m2. The highest average C-organic content in all sites was forwad on the root of the seagrass with a value of 27.76%. Relationship between carbon stroge and density of seagrass is best stronge y =16.11+15.56x;R² = 0.89; r = 0.79. Keywords: Global Warming, Seagrass, Biomass, C-organic